IMPLEMENTASI TEKNOLOGI RFID (RADIO FREQUENCY IDENTIFICATION) UNTUK RECORDING DATA TERNAK SAPI - Ratna Aisuwarya; Budi Rahmadya; Mohammad Hafiz Hersyah; Rahmi Eka Putri; Rian Ferdian; Fitri Ardiani (Jurnal Hilirisasi IPTEKS, 2019)
Every year there is an increase in the need for cattle. Efforts to meet beef and milk consumption needs to achieve beef self-sufficiency programs contained in the 2015-2019 National Medium-Term Development Plan (RPJMN) target, one of which is to implement maintenance management on farms in the form of recording or recording livestock data and important information concerning livestock. Recording will make it easier to make the right decisions for programs to improve the quality of cattle production and increase the number of cows. In this service activity, RFID is used to identify cattle in the recording process by integrating android applications and website applications. The process of recording cattle data will be carried out through an android application in the form of recording for cow identity, cattle ownership, cow health, insemination process in cattle, calf birth, and cattle growth data and sending data to the database. The activity was carried out in Padang Mangateh Ranch, Lima Puluh Kota Regency, Alam Serambi Lembu Farmers Group, Padang Panjang.